2020
DOI: 10.3390/nu12092862
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns, Carbohydrates, and Age-Related Eye Diseases

Abstract: Over a third of older adults in the U.S. experience significant vision loss, which decreases independence and is a biomarker of decreased health span. As the global aging population is expanding, it is imperative to uncover strategies to increase health span and reduce the economic burden of this age-related disease. While there are some treatments available for age-related vision loss, such as surgical removal of cataracts, many causes of vision loss, such as dry age-related macular degeneration (AMD), remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 109 publications
0
39
0
Order By: Relevance
“…All published epidemiologic studies indicate that people who consume lower glycemic index diets are protected against AMD, and even against the progression of AMD [132,133]. Consistent with these data, the more one subscribes to a Mediterranean, lower glycemic index diet, the better the protection against early or late AMD [134].…”
Section: The Involvement Of Glyoxalase System In Aging and Age-related Diseasesmentioning
confidence: 66%
“…All published epidemiologic studies indicate that people who consume lower glycemic index diets are protected against AMD, and even against the progression of AMD [132,133]. Consistent with these data, the more one subscribes to a Mediterranean, lower glycemic index diet, the better the protection against early or late AMD [134].…”
Section: The Involvement Of Glyoxalase System In Aging and Age-related Diseasesmentioning
confidence: 66%
“…About 196 million are getting affected by it all over the world. It can be controlled with the healthy alteration in diet and lifestyle [28,29].…”
Section: Prevalence Of Amdmentioning
confidence: 99%
“…Processing vegetables beyond a certain limit results in the destruction of the essential vitamins in them, which will have made it much better to consume the leafy vegetables in raw form. Eating food having high level of sugar like sweets over a certain limit is bad for health similarly consuming food rich in fats and oils adds into the category of unhealthy diet [28]. Poor dietary habits, like consumption of a lot of energy bars, drinks, junk food and fried food, lead to high prevalence of Age-related macular disorders.…”
Section: Prevalence Of Amdmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural food and its derivatives play essential roles in health and wellbeing, and it has been characteristically associated with defense mechanisms against microbial agents, xenobiotics and/or physical factors, also demonstrating an immense range of health-promoting perspectives for achieving a pleasant lifespan [33,34]. Large population studies on the role of nutrition in eye health have reported controversial results over decades, mainly regarding cataracts, AMD, RD, OSD/DED, and glaucoma, and also slowing progression of the above sight-threatening diseases, by dietary interventions has also been discussed [6,8,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: State Of the Artmentioning
confidence: 99%